2022
DOI: 10.1038/s41467-022-32051-3
|View full text |Cite
|
Sign up to set email alerts
|

A reconfigurable and magnetically responsive assembly for dynamic solar steam generation

Abstract: Interfacial solar vapor generation is a promising technique to efficiently get fresh water from seawater or effluent. However, for the traditional static evaporation models, further performance improvement has encountered bottlenecks due to the lack of dynamic management and self-regulation on the evolving water movement and phase change in the evaporation process. Here, a reconfigurable and magnetically responsive evaporator with conic arrays is developed through the controllable and reversible assembly of gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(40 citation statements)
references
References 53 publications
0
40
0
Order By: Relevance
“…Figure c shows the magnetic hysteresis loops of Fe 3 O 4 nanoparticles and the PDMS@Fe 3 O 4 composite. Misaligned hysteresis loops were obtained for both materials (Figure c), implying that both are ferromagnetic . As a result of the ferromagnetism, deposited PDMS@Fe 3 O 4 during spraying is magnetized under the external magnetic field .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Figure c shows the magnetic hysteresis loops of Fe 3 O 4 nanoparticles and the PDMS@Fe 3 O 4 composite. Misaligned hysteresis loops were obtained for both materials (Figure c), implying that both are ferromagnetic . As a result of the ferromagnetism, deposited PDMS@Fe 3 O 4 during spraying is magnetized under the external magnetic field .…”
Section: Resultsmentioning
confidence: 95%
“…Misaligned hysteresis loops were obtained for both materials (Figure 1c), implying that both are ferromagnetic. 22 As a result of the ferromagnetism, deposited PDMS@Fe 3 O 4 during spraying is magnetized under the external magnetic field. 23 The relative permeability of PDMS@Fe 3 O 4 is 1.21, which means that the induced magnetic field strength in the deposited needle-like structure is higher than that of the background, as simulated in Figure 1c and Figure S2 of the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…189 Recently, Qu's group developed hybrid graphene-wrapped Fe 3 O 4 nanoparticles to further fabricate a reconfigurable and magnetically responsive conic-array evaporator. 190 Under the applied variable magnetic field, the evaporator could achieve a dynamic evaporation process with a 23% higher evaporation rate than that of the static evaporation process, stemming from improved water vapor diffusion. It was demonstrated that the synergistic effect of hybrid graphene and Fe 3 O 4 materials endowed the evaporator with distinct properties.…”
Section: Isvg Systems: Materials and Fabrication Techniquesmentioning
confidence: 99%
“…Therefore, recent research has focused on designing devices with different structures. 9,13–15 For example, the WE area has been increased by introducing a well-designed three-dimensional (3D) evaporator, 16–18 allowing additional energy to be absorbed from the surroundings, thereby effectively increasing the PCE beyond the theoretical limit. 19–23…”
Section: Introductionmentioning
confidence: 99%